1998
DOI: 10.1074/jbc.273.32.20504
|View full text |Cite
|
Sign up to set email alerts
|

V-ATPase of Thermus thermophilus Is Inactivated during ATP Hydrolysis but Can Synthesize ATP

Abstract: The ATP hydrolysis of the V 1 -ATPase of Thermus thermophilus have been investigated with an ATP-regenerating system at 25°C. The ratio of ATPase activity to ATP concentration ranged from 40 to 4000 M; from this, an apparent K m of 240 ؎ 24 M and a V max of 5.2 ؎ 0.5 units/mg were deduced. An apparent negative cooperativity, which is frequently observed in case of F 1 -ATPases, was not observed for the V 1 -ATPase. Interestingly, the rate of hydrolysis decayed rapidly during ATP hydrolysis, and the ATP hydroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 45 publications
4
79
0
Order By: Relevance
“…Alternatively, the loss of activity is suggestive of product inhibition, which could also be an effective means of minimizing unproductive ATP hydrolysis in vivo. Similar behavior of the M. sexta cytosolic V 1 has been attributed to product inhibition (14), and a more detailed analysis of the V 1 -ATPase of Thermus thermophilus (44) has clearly demonstrated that this enzyme can be inactivated during ATP hydrolysis by entrapping an inhibitory MgADP at the catalytic site. In both of these cases, the similarity to entrapping of MgADP by F 1 -ATPases has been noted, but there are also some important differences between the behavior of the yeast cytosolic V 1 complexes and F 1 -ATPases (32,(35)(36)(37).…”
Section: Figmentioning
confidence: 84%
“…Alternatively, the loss of activity is suggestive of product inhibition, which could also be an effective means of minimizing unproductive ATP hydrolysis in vivo. Similar behavior of the M. sexta cytosolic V 1 has been attributed to product inhibition (14), and a more detailed analysis of the V 1 -ATPase of Thermus thermophilus (44) has clearly demonstrated that this enzyme can be inactivated during ATP hydrolysis by entrapping an inhibitory MgADP at the catalytic site. In both of these cases, the similarity to entrapping of MgADP by F 1 -ATPases has been noted, but there are also some important differences between the behavior of the yeast cytosolic V 1 complexes and F 1 -ATPases (32,(35)(36)(37).…”
Section: Figmentioning
confidence: 84%
“…Aliquants of purified protein were frozen in liquid nitrogen and stored at −80°C. Because no nucleotide was added during the purification procedure, the preparation of enzyme is presumed to be in a nucleotidefree state (23,50). Purified V-ATPase showed >95% N,N'-dicyclohexylcarbodiimide (DCCD) sensitivity in ATPase assays (51).…”
Section: Methodsmentioning
confidence: 99%
“…In eukaryotic cells, V 0 V 1 -ATPases exist in both intracellular compartments and plasma membranes, and are responsible for the acidification of intracellular compartments, renal acidification, born resorption, and tumor metastasis (2). On the other hand, most prokaryotic V 0 V 1 -ATPases produce ATP using the energy of a transmembrane proton electrochemical gradient that is generated by a respiratory chain (4,5).…”
mentioning
confidence: 99%
“…The V 0 V 1 -ATPase is capable of both ATP-driven proton translocation and proton-driven ATP synthesis and functions as ATP synthase in vivo (5,23 (Table I). Although the molecular size of some subunits of T. thermophilus is smaller than that of eukaryotic counterparts, each subunit of T. thermophilus shows a sequence similarity to its eukaryotic counterpart (see Table I).…”
mentioning
confidence: 99%